Analysis of IL10 haplotypic associations with severe malaria. - Wilson, J; Rockett, K; Jallow, M; Pinder, M; Sisay-Joof, F; Newport, M; Newton, J; Kwiatkowski, D (2005)
We investigated the association between severe malaria and genetic variation of IL10 in Gambian children, as several lines of evidence indicate that IL10 is protective against severe malaria and that IL10 production is genetically determined. We began by identifying five informative SNPs in the Gambian population that were genotyped in a combined case-control and intrafamilial study including 654 cases of severe malaria, 579 sets of parents and 459 ethnically matched controls. No significant associations were identified with individual SNPs. One haplotype of frequency 0.11 was strongly associated with protection against severe malaria in the case-control analysis (odds ratio 0.52, P=0.00002), but the transmission disequilibrium test in families showed no significant effect. These findings raise the question of whether IL10 associations with severe malaria might be confounded by foetal survival rates or other sources of transmission bias.